Student Interest Development Through Dance Art Extracurricular Activities at SMA Negeri 6 Sijunjung - Elga Pratiwi Rahmadani; Mansyur, Herlinda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study was to reveal and describe about the development of student interest through dance art extracurricular in Sijunjung State High School. The type used in this study is qualitative research through descriptive method. The object of this study was to directly observe the development of student interest carried out on dance art extracturcurricular at Sijunjung State High School, which followed by 30 students from class X and XI. The types of data used are primary data and secondary data in which the researcher itself as a research instrument. Data collection techniques through literature studies, observations, interviews and documentation. The results showed that the development of student interest through dance art extracurricular in the State High School 6 Sijunjung gave students a chance to develop themselves and express themselves in accordance with the interests of students in the dance art sector. Through planning, implementation and evaluation designed by schools and teachers, in the development of students of this activity is an effort in forming students’ character and personality, including cooperation, solidarity and creativity. The supporting factor for the implementation of dance art extracurricular at the 6 Sijunjung State High School is the availability of facilities and infrastructure, quality of coaches, interest in students and support from the school. The retardation factor is the absence of students’ platitude so that students slowly understand the dance moves given coaches.